Security model based mobile agent for mobile ad hoc networks. (2019) - Ahmed, Maqbol; Okba, Kazar; Abdelbasset, Barkat; Mouadh, Bali
In this paper, we propose a security model based mobile agent for MANETs, the objective here is to improve the security level of the network communication without affecting its performance. The model includes a hierarchical clustering and mobile agents. We apply the concept of dominating set based clustering for partitioning the network into clusters. The cluster head election is based on both the trust and resources ability of the node. We define four agent types. The node agent manages the use of node resources. The ambassador agent is created by the control agent to monitor all the actions of the node agent. The control agent is created in the most trusted with best resources node to control the communication into the cluster and participates with its counterparts in the security network completely, and the transporter agent carries the encrypted information in the network.